Modeling effects of abiotic and anthropogenic factors to rice production - A case study in Sapa district, Lao Cai province, Vietnam - Bac, Dang Kinh; Burkhard, Benjamin (Vietnam Journal of Earth Sciences, 2020)
The famous terraced rice ecosystem in the mountainous areas as Sapa of northern Vietnam has expanded with unstable productivity over generations. However, the question arises of how natural and human conditions on terraces can boost the quality of rice provisioning ecosystem service supply with rice yields as an indicator. The study used a semi-structured interview method, the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) tool and general linear models to investigate the influence of natural and human-derived components on the rice provisioning service at six villages. The results showed that along with the importance of applying a fertilizer-based system in the terraced rice ecosystem, topology- and hydrology-based systems have been influencing significantly on water and nutrient supply for irrigation on terraced rice fields. Moreover, analyzing the natural components has been considered more efficient than human-derived components for a sustainable rice ecosystem. The results indicated that the high potential of rice provisioning service supply had found at the downstream of Ta Van sub-catchment and the Vu Lung Sung village where the distance from paddy fields to sinks or outlet of streams is lower than five kilometers. The last result of the synthetic model proving 74.28 percent of deviance of terraced rice production did not avoid many noises in collecting and standardizing data that also discuss in this study.